1999
DOI: 10.1177/106591299905200405
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Executive Orders: Legislative Constraints on Presidential Power

Abstract: Conventional wisdom suggests that Presidents use executive orders, sometimes characterized as presidential legislation, when legislation is too difficult to pass (in the face of an opposition Congress, for example) or when executive departments or agencies tend to embrace their congressional patrons, rather than the White House. According to this model, executive orders are strategic instruments used by a President to circumvent the constitutionally prescribed policymaking process. Recently studies have found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 26 publications
5
101
1
Order By: Relevance
“…Theoretically, we extend Howell's (2003) rich framework, which remains the principal nonverbal, formal treatment of unilateralism (see also Deering and Maltzman 1999;Moe and Howell 1999), to build competing models associated with more and less presidential influence. Per our description of formal approaches, Howell's framework has presidents moving first in a game, allowing them to circumvent the legislature when there is either gridlock or no congressional incentive to move policy given the presidential preference and status quo.…”
mentioning
confidence: 99%
“…Theoretically, we extend Howell's (2003) rich framework, which remains the principal nonverbal, formal treatment of unilateralism (see also Deering and Maltzman 1999;Moe and Howell 1999), to build competing models associated with more and less presidential influence. Per our description of formal approaches, Howell's framework has presidents moving first in a game, allowing them to circumvent the legislature when there is either gridlock or no congressional incentive to move policy given the presidential preference and status quo.…”
mentioning
confidence: 99%
“…The greater number of party seats translates into a greater capacity for the president to draw upon members of his own party to influence policies. Scholars have suggested that the greater the president's party seats in Congress, the less likely he will need to issue executive orders to influence policy (Deering & Maltzman, 1999;Krause & Cohen, 1997). Drawing upon our earlier argument relating to issue distinctions, we expect the number of party seats in Congress to influence presidential decisions to issue executive orders on domestic policy but not in the area of foreign policy.…”
Section: Issue Differences: Expectationsmentioning
confidence: 83%
“…Our results support this view, but only in the area of foreign policy. Other scholars have argued that presidents issue more executive orders when they are unable to achieve victories in the legislature (Deering & Maltzman, 1999;Light, 1982). In other words, they use executive orders to make policy when the going gets tough in Congress.…”
Section: Data and Results: The Statistical Modelsmentioning
confidence: 99%
“…For example, recent research suggests presidential rhetoric is a policy making instrument to expand presidential power (Rottinghaus and Maier, 2007) and can set the country's agenda (Kingdon, 1995). Presidential power can be utilized in differing ways without the consent of Congress, the courts, and the public, by signaling to the public through rhetoric a focus and a possible future agenda (Elsea, 2003;Deering and Maltzman, 1999).…”
Section: Leadership and Leader Rhetoricmentioning
confidence: 99%